Genome scanning by composite likelihood - Collins, Andrew (Henry Stewart Talks, 2007)
The nature of complex traits and introduction to linkage and association mapping, Measures of linkage disequilibrium, Methodology for constructing linkage disequilibrium maps and their properties, Application to different human populations and relevance of linkage patterns/population bottlenecks, Association mapping, Importance of linkage disequilibrium structure, Methodology for association mapping and interpretation of patterns of association, Applications to example datasets and contrast with msSNP approach
Archived at 2021/02/25